2013
DOI: 10.1111/ncn3.48
|View full text |Cite
|
Sign up to set email alerts
|

Patient with insidious hypoactive delirium associated with pregabalin

Abstract: Pregabalin has favorable effects on several types of neurological pain, but can cause side-effects including dizziness, somnolence and delirium. Delirium presents as two variants in terms of psychomotor disturbance: the hyperactive type, showing agitation and vigilance; and the hypoactive type, showing lethargy and decreased motor activity. Patients with delirium associated with pregabalin therapy have been reported to experience hyperactive delirium. Here, we report the case of a 68-year-old patient with insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Even short duration low doses of pregabalin (75 and 150 mg for 3-7 days) have the potential to initiate hyperactive delirium [14,15]. A further study showed the occurrence of insidious hypoactive delirium in a patient receiving just 100 mg of pregabalin [16].…”
Section: Discussionmentioning
confidence: 96%
“…Even short duration low doses of pregabalin (75 and 150 mg for 3-7 days) have the potential to initiate hyperactive delirium [14,15]. A further study showed the occurrence of insidious hypoactive delirium in a patient receiving just 100 mg of pregabalin [16].…”
Section: Discussionmentioning
confidence: 96%
“…The most exposed are older patients with comorbidities, but delirium has also been reported in the youth. Pregabaline-induced delirium mostly occurs when it is used in high doses to relieve neuropathic pain, but it may also occur at doses up to 100 mg [56,57]. Withdrawal from pregabaline also induces delirium, so the dose of pregabaline should be gradually reduced over a minimum of one week.…”
Section: Pregabaline -Induced Deliriummentioning
confidence: 99%
“…5 Delirium, psychosis, and visual hallucinations have been reported as potential adverse effects of the use of gabapentinoids. 6 , 7 Nonetheless, few case studies chronicle these symptoms associated with pregabalin. 8 This article details the case of an older woman who developed delirium after experiencing pregabalin withdrawal.…”
Section: Introductionmentioning
confidence: 99%